Mempromosikan Wisata Kuliner Di Kota Mataram Melalui Media Sosial, Peluang Dan Tantangan - Harnika, Ni Nyoman; Sutama, I Wayan (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2023)
Tourism is a sector that continues to develop and provides great benefits for development progress. The presence of social media has played a role in bringing about fantastic leaps of progress, including in tourism promotion. Culinary tourism is one of the attractions of a destination. This article aims to explore the use of social media as an effective marketing strategy while improving the image of tourism in the city of Mataram. Using qualitative methods, it was concluded that opportunities: the existence of social media to promote culinary tourism is related to its wide-reaching nature, it can display unique and interesting visual content created by collaborating with influencers to improve the tourist experience. Challenges: excess information and noise, difficulty in maintaining authenticity or original taste, difficulty managing images on social media, and a lack of digital skills and resources. Culinary tourism locations in Mataram City, which include the Karang Taliwang area, Ampenan Beach, Loang Balok Beach and the Rembiga area, need attention from the government regarding representative arrangements. Development of the tourism sector that is oriented towards sustainable tourism by involving the community must be carried out through strategic policies that lead to increasing community income.